Micropropagation of ornamental plants: a review on Nepalese protocols - Sandip Timilsina; Amisha Poudel; Nishes Ghimire; Santosh Neupane; Puspa Raj Poudel (Cogent Food & Agriculture)
Ornamental plants are primarily cultivated for their aesthetic value, and their demand is rapidly increasing in Nepal. Among them, orchids are especially popular with Nepalese nursery growers due to their high market value; however, they exhibit poor multiplication under natural conditions. This limitation has led to the need for tissue culture techniques to enable rapid multiplication. This review aims to highlight and summarize the current status of tissue culture and the protocols followed for the propagation of ornamental plants in Nepal. The primary sources of explants for the propagation of these crops are seeds and shoot tips. Murashige and Skoog (MS) medium is widely used as the culture medium, while the plant growth regulators 6-benzylaminopurine (BAP) and 1-naphthalene acetic acid (NAA) are commonly used to promote growth and development. Acclimatization success varies depending on the plant species and the substrate used, with survival rates ranging from 70% to 98%.